Pediatric Brain Tumor Risk Associated with Head Computed Tomography: Systematic Literature Review - Dilara R. Kuznetsova; Diana A. Gabdullina; Alina F. Makhmudova; Elena V. Bochkina; Elizaveta O. Platonova; Bogdan O. Zhirnov; Elnara E. Akhmetgareeva; Liliya S. Atangulova; Ruslan S. Shein; Kristina I. Rakhimova; Vlastilin V. Pakalnis; Elza R. Ganieva (Вопросы современной педиатрии, 2023)
Computed tomography (CT) of the brain has changed diagnostic neuroradiology significantly over the past 50 years since it was firstly used back in 1971 to visualize suspected frontal lobe tumour. The safety of head CT is determined by the small amount of radiation and the low sensibility of brain tissue to cytotoxic damage due to ionizing radiation compared to other organs. However, some population groups may be at increased risk. Thus, children are more susceptible to radiation cancer than adults and lifelong attributive risk (LAR) can be more than 10 times higher for an infant than for a middle-aged adult. The authors have reviewed published studies that examined the prevalence and mortality of intracranial tumors in children undergoing head CT in comparison to unaffected individuals. Electronic search of publications in the PubMed database from 1966 to date was carried out. We have carried out intersectoral search for documents containing keywords or medical subject headings (MeSH) related to three wide categories: 1) computed tomography, 2) radiation-induced tumors, 3) risk, morbidity or epidemiology. Further search was performed in manual mode. Available epidemiological data generally confirmed correlation between head CT and tumor growth induction. Thus, current epidemiological data accept the opinion that the risk of tumor induction associated with head CT in children is very small (one tumor per 3,000–10,000 studies). The minimal estimated risk of tumor induction due to head CT in children is mostly offset by its diagnostic imaging benefits considering the clinical indications to minimize radiation dose. Understanding and quantitative risk assessment of carcinogenesis associated with CT imaging led to dose reduction in pediatric CT protocols. This trend should continue and should be implemented in all age groups. Although the decision to perform head CT is often undeniable (injury or hemorrhage), careful assessment of studies frequency is required, especially in patients who need disease monitoring. Cumulative effect in such cases may increase the minimal risk of carcinogenesis. Larger and advanced epidemiological studies are required to better understand these risks.